A convergent synthetic platform of gold/silica nanomaterials functionalized gelatin/chitosan hydrogel framework for the bone fracture treatment. Issue 1 (31st December 2022) - Lin, Meng; Zhang, Jiangnan; Li, Jun; Zhang, Dechun; Mo, Tingting
Abstract: To establish a gold/silica hybrid, nanomaterials (Au/SiO2 ) were incorporated into a gelatin methacrylate/chitosan matrix. By using FESEM, compressive strength testing, and conductivity/resistance measurements on gelatin (G)/chitosan (C), G/C-Au@SiO2 hydrogels developed. Biocompatibility investigations on osteoblasts MG-63 cells were carried out to determine whether the cell was compatible with the conductive hydrogel as it had been created. The results indicated that HNPs had improved compressive strength and conductivity without losing the favourable features such as biodegradable nature and porous shape of G/C hydrogel. The mechanical properties and Elastic modulus of composites hydrogels were enhanced twofold when hybrid nanomaterials were added to the mixture. The cyclic compressive analysis shows that pure G/C hydrogels lost their mechanical stability within the first few cycles, but G/C-Au@SiO2 hydrogels lasted for up to fifty cycles. It was demonstrated that osteoblast proliferation and adhesion were increased on the hydrogel in the CCK-8 experiment. Further, the cell survival of the hydrogels with G/C-Au@SiO2 conductivity was enhanced by 15% compared to that of pure G/C hydrogels. The morphological features of the MG-63 cells experiments were performed by using a Fluorescein diacetate hydrolysis (FDA) staining assay. This work offers a unique method for enhancing mechanical integrity and electrical properties in gelatin-based G/C hydrogels by adding bifunctional hybrid nanomaterials (HNPs) for bone fracture tissue engineering applications. Graphical Abstract: UF0001